Developing young professionals' collaborations in the Americas - Solís Calvo, Luis Fernando (2023)
Health Equity Network of the Americas (HENA) and Young WFPHA to mobilize young professionals in Latin America. The key lines of action include joint research projects, developing an ambassador program, creating internship opportunities, and facilitating partnerships. The presentation details the process of identifying groups of young professionals through consultations and campaigns. It also summarizes a successful meeting for young professionals, highlighting participation from various countries and institutions and discussing priorities for the health equity agenda. The next steps involve meeting with other key organizations and planning a second regional encounter.